Evaluasi Program pendidikan Kewirausahaan Melalui Tteaching Factory di SMK SMTI Bandar Lampung - fathiannisa sabila; Elais Retnowati; Kamalludin (Program Studi Manajemen Pendidikan, 2020)
Abstract::The research has been conducted to evaluate the suitability of the entrepreneurship education program through the Teaching Factory at SMK SMTI Bandar Lampung, including the planning, implementation and outcome stages. This research uses a qualitative method with a Stake Evaluation approach (Antecedents, Transactions and Outcomes). The main subjects of this research consisted of Headmaster, Entrepreneurship Teachers, Supervisors of Teaching Factory, Industrial Partners, Customers of Products, Students and the Communities. The data were collected using interview methods, observation, and documentation. Our finding indicates that the implementation of entrepreneurship education programs through the teaching factory is went quite decent. This could be seen by the results of the evaluation showing that the Antecedent (preparation) aspect is in the inappropriate category, whereas the Transaction (implementation) and the Outcomes aspect are in the appropriate category. Furthermore, improving the quality of the program could be done by improving the inappropriate category aspects for each evaluation stage. Keywords: Evaluation of program, Entrepeneurship of education, Teaching Factory, Countenance Stake Model.